Aislamiento e identificación de bacterias potenciales que degradan Alfa-cipermetrina y Dimetoato de suelos agrícolas con cultivos de arroz (Oryza sativa L) en la provincia de Los Ríos - Andrade Lugo, Nicole Carolina (2021)
Considerando que el arroz es uno de los cultivos más popularizados es de suma importancia realizar estudios sobre la contaminación de dichos suelos con el fin de mejorar y remediar sus propiedades para evitar su degeneración. Por este motivo, este estudio tuvo como objetivo principal la selección y caracterización de bacterias con mejor potencial degradador de Alfa cipermetrina y Dimetoato, los cuales constituyen parte de la lista de insecticidas más comercializados en la provincia. Para la obtención de cepas tolerantes se aisló las mismas de muestras de suelo de cultivos de arroz que habían recibido continuas aplicaciones de los plaguicidas. Se obtuvo seis cepas de las cuales cuatro (C1Al, C2Al, C1DI y C2DI) presentaron un mejor nivel de tolerancia. La caracterización bioquímica mostró que sólo dos aislamientos fueron positivos para catalasa (C1Al y C2DI), todas las cepas fueron bacilos Gram negativos, y se identificaron como Delftia sp., Sphingobium sp y Novosphingobium aromaticivorans. El crecimiento bacteriano y degradación aumentó a medida que las concentraciones de ambos pesticidas aumentaron de 0 a 600 ppm tanto en cultivo sólido como líquido en todas las cepas. Se halló que el tipo de plaguicida y la concentración afectaron la capacidad de crecimiento y mineralización de los pesticidas, obteniendo mejores resultados con alfa cipermetrina que mostró la tasa de eliminación más alta de 3,608% a 96 h en concentraciones de 600 ppm. Palabras clave: • BIODEGRADACIÓN • ALFA CIPERMETRINA • DIMETOATO • CULTIVO DE ARROZ • BIORREMEDIACIÓN Abstract Agricultural production is intended to produce food, for commercialization in local and national markets. Farmers apply pesticides out of the need to protect their crops, without considering the toxicity of the product that leads to contamination by chemical residues to the crops, which affects the soil. The need to restore soils in many growing areas through bioremediation has become the current focus of environmental biotechnology and microbiology with microorganisms that remedy the damage caused. Considering that rice is one of the most popular crops, it is extremely important to carry out studies on the contamination of these soils to improve and remedy their properties to prevent their degeneration. For this reason, the main objective if this study is the selection and characterization of bacteria with the best degradation potential of Alpha cypermethrin and Dimethoate, which constitute part of the list of the most commercialized insecticides in the province. To obtain tolerant strains, they were isolated from soil samples of rice crops that had received continuous applications of pesticides. Six strains were obtained, of which four (C1Al, C2Al, C1DI and C2DI) presented a better level of tolerance. The biochemical characterization showed that only two isolates were positive for catalase (C1Al and C2DI), all the strains were Gram negative bacilli, and were identified as Delftia sp., Sphingobium sp and Novosphingobium aromaticivorans. Bacterial growth and degradation increased as the concentrations of both pesticides increased from 0 to 600 ppm in both solid and liquid culture in all strains. It was found that the type of pesticide and the concentration affected the growth capacity and mineralization of the pesticides, obtaining better results with alpha cypermethrin, which showed the highest elimination rate of 3.608% at 96 h at concentrations of 600 ppm.